Saubhagya: An Online Food Donation Platform for Ending Hunger and Malnutrition in Sri Lanka - G.H.T.R. Irushika; K.V.M. Wijesinghe; P.K.I. Udeshika; J.J. Sathsara; D. I. De Silva; R.R.P. De Zoysa (Buana Information Technology and Computer Sciences (BIT and CS), 2023)
Hunger and malnutrition continue to be significant challenges in developing nations, including Sri Lanka. To address this issue, the research paper presents "Saubhagya," an online web application that provides a platform for social assistance. The platform allows individuals to donate food and groceries to needy organizations such as blind, deaf, orphanages, making it a user-friendly and effective solution. Users are required to register as food donators, needy people(organizations), partners and food collection agents. The system connects these user groups when necessary, ensuring a smooth and efficient process. One unique feature of "Saubhagya" is its live capability of tracking food collection and delivery using GPS and Google Maps. This feature ensures that food donations are delivered to the right organizations promptly, promoting transparency, accountability, and communication among users. The research paper aims to evaluate the effectiveness of "Saubhagya" in reducing hunger and malnutrition in Sri Lanka through user feedback and system performance metrics. If successful, the platform can be scaled to other developing nations facing similar challenges. This research demonstrates the potential of digital platforms in addressing social and environmental challenges. By leveraging technology, collective action can be harnessed to create positive social impact. "Saubhagya" represents a significant step forward in the fight against hunger and malnutrition, and it is hoped that it can inspire others to use technology to address pressing global issues.